Apakah Promosi Islami dan Hedonic Shopping Motivation Mempengaruhi Perilaku Impulsive Buying Generasi Z? - Azid, Raka Malik; Machfudz, Masyhuri (Al-Tijary, 2023)
The emergence of Muslim fashion in Banyuwangi can be attributed to the inclination of the Z generation to utilize e-commerce platforms for fashion shopping, hence promoting impulsive purchasing behavior. The current study aims to examine how the perception of islamic promotion and hedonic shopping motive influence impulse purchase, with happy emotions serving as a mediator in the context of Muslim fashion products. This study focuses on clients belonging to Generation Z in Banyuwangi Regency who have made purchases using e-commerce platforms. This study employs a quantitative research design with an explanatory approach. It has a sample size of 100 participants selected using purposive sampling methods. The survey results obtained through an online questionnaire with a Likert scale were subsequently analyzed using path analysis in SPSS. The findings of this study indicate that employing Islamic advertising and hedonic impacts can enhance consumers' favorable emotions towards Muslim fashion products via e-commerce. Furthermore, the indirect impact of favorable emotions serves as a mediator for the effect of of islamic promotion on impulsive purchasing. However, it is important to note that various good emotions do not mediate the relationship between hedonic shopping incentive and impulsive purchase. This research has implications for the implementation of marketing strategies for business people who use e-commerce platforms.